Mindfulness, complex interventions and conceptual clarity. Issue 9 (29th May 2020) - Hancock, Jason; Mattick, Karen
Abstract : How can we further develop mindfulness training in health professions education? Hancock and Mattick argue the answer lies in the complex interventions framework.